Protein disulfide isomerase family 6 promotes the imatinib-resistance of renal cell carcinoma by regulation of Wnt3a-Frizzled1 axis - Yong Huang (Taylor & Francis Group, 2021)
Imatinib is a nontoxic tyrosine kinase inhibitor, used in the treatment of advanced renal cell carcinoma. However, some patients with renal cell carcinoma develop resistance to imatinib. Protein disulfide isomerase family 6 (PDIA6) was involved in the chemo-resistance of lung adenocarcinoma. The effect of PDIA6 on imatinib-resistance of renal cell carcinoma was investigated in this study. Firstly, PDIA6 was found to be up-regulated in the imatinib-resistant renal cell carcinoma tissues and cells. Functional assays showed that knockdown of PDIA6 sensitized imatinib-resistant renal cell carcinoma cells to imatinib through decreasing the half-maximal inhibitory concentration (IC50) of imatinib-resistant renal cell carcinoma cells. Secondly, cell proliferation of imatinib-resistant renal cell carcinoma cells was suppressed by PDIA6 silencing, and the apoptosis was promoted with reduced Bcl-2, enhanced Bax and cleaved caspase-3. Moreover, interference of PDIA6 increased phosphorylation of H2A histone family member X (γH2AX), while decreased Rad51 and phosphorylated DNA-dependent protein kinase (DNA-PK) (p-DNA-PK) in imatinib-resistant renal cell carcinoma cells. Lastly, protein expression levels of Wnt3a and Frizzled1 (FZD1) in imatinib-resistant renal cell carcinoma cells were down-regulated by silencing of PDIA6. Over-expression of FZD1 attenuated PDIA6 silencing-induced increase in cell apoptosis and decrease in cell proliferation in imatinib-resistant renal cell carcinoma cells. In conclusion, knockdown of PDIA6 sensitized imatinib-resistant renal cell carcinoma cells to imatinib through inactivation of Wnt3a-FZD1 axis.